Strawmanning in Academic Discourses: Cases from Infamous Dichotomies in Education and Developmental Psychology - Ahmad Junaidi (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
With the flooding number of scholarly texts and public commentary, it is crucial to maintain the healthy academic discourses within the academic texts. One particular aspect that has been overlooked is the presence of hasty commentaries made by proponents of a theory when commenting about other theories or other stances. This academic commentary article analyses the presence of cases of strawmanning within the field of education and developmental psychology in order to raise awareness among novice academics and intellectuals on the merit of cautions and carefulness in criticising, representing, and interpreting a theory. Using a qualitative descriptive analysis on two major cases of strawmanned interpretations of teacher-led instruction and piagetian theory, this study categorises the factors driving the emergence of intentional and unintentional strawmanning. It is argued that surface reading and convenience dominate the cases of strawmanning cases in novice and amateur academic environments.